Learning Motivation: Strategies to Increase Students' Engagement in Online Learning at San Sebastian College-Recoletos, Manila - Ma Lourdes Narca; Dennis G. Caballes (International Journal of Asian Education, 2021)
The objective of this study is to be able to find ways or the best strategies in teaching that will motivate students to exert effort in their studies, considering the present conditions in this pandemic period. A quantitative method was used to define the study's objective, where two sections of Psychology students who took up Science 101 and Science 104 were chosen as respondents to answer the survey questionnaire through google forms. The purposive sampling technique was also employed since these students can appropriately answer the queries sent to them. The Likert scale method was used to measure the students' level of agreement, with the 5-point range, where the results were collated and analyzed.  The research result finds several strategic activities such as report enhancement, online debates, virtual experiments, discussion and updating of recent findings, and the creation of infomercials that truly captured their interest and attention. This study made use of several references and tables in order to support the results obtained. The researcher recommends that there should be effective and efficient motivational activities to sustain student engagement. The researchers, who are also educators, have agreed to continuously upgrade the newfound motivational activities to encourage more students to study well even in an online setting, thus giving more opportunities for better achievement in education.